Diploid Ancestor Tracing of Allopolyploid Cultivars in Camellia reticulata Based on ITS and RPB2 Sequences - Zhifeng Fan; Wei Zheng; Chengmin Yan; Xiaodan Xu (Horticulturae, 2025)
Camellia reticulata is a well-known ornamental species with a type specimen that is an allohexaploid, possibly descended from diploid ancestors like C. saluenensis, C. pitardii, and diploid C. reticulata. With over 1500 years of cultivation, heritage C. reticulata cultivars show varied ploidy levels, including hexaploid, octoploid, and decaploid forms, though their diploid ancestors are still unidentified. This study aims to trace these diploid ancestors by cloning and sequencing ITS from 25 taxa and RPB2 from 21 taxa across various ploidy levels of C. reticulata and its traditional cultivars and related species, combined with their fruit morphology data. Analyses of the ITS and RPB2 sequences suggest that the diploid ancestors of C. reticulata and its traditional cultivars may include C. saluenensis, C. pitardii, and diploid C. reticulata, while excluding C. mairei and C. polyodonta. Morphological analysis showed that diploid C. reticulata has significantly larger fruit weight, diameter, and pericarp thickness compared to C. pitardii, C. saluenensis, and both tetraploid and hexaploid C. reticulata. Since diploid ancestors of allopolyploids are often classified as distinct taxa, we suggest that diploid C. reticulata be recognized as a new variety of C. pitardii, as its ITS sequences are closely aligned with C. pitardii. This study offers key insights into the origin, evolution, and breeding of C. reticulata.